Intercropping efficiency of chickpea (Cicer arietinum) based intercropping system under rainfed condition of Bihar - Alam, M.I. (Annals of Agricultural Research, 2016)
An experiment on Intercropping efficiency of chickpea (Cicer arietinum) based intercropping system under rainfed condition was carried out during rabi-seasons of 2009-10 and 2010-11 at Dholi farm of Rajendra Agricultural University, Pusa, (Samastipur), Bihar. Among the row ratio in intercropping systems, chickpea + linseed (6:1) expressed equal yield attributes and grain yield, and harvest index of chickpea than the chickpea + mustard in 6:1 and 6:2 ratio during both the years. The yield attributes, grain and straw yields, and harvest index of chickpea did not vary significantly due to fertilizer levels. The yield attributing characters of mustard and linseed were higher at 6:1 row ratio of intercropping than sole crops. The 6:2 row ratio of chickpea + mustard and chickpea + linseed recorded maximum grain and straw yields of mustard and linseed which were significantly higher over their 6:1 row ratio in both the years. Application of 100% and 75% RDF recorded similar grain yields of mustard and linseed and both turned significantly superior over 50% RDF in both the years. Chickpea + mustard irrespective of their row ratios recorded significant reduction in number of Helicoverpa larvae/10 plants, number of damaged pods/plant and pod damage percentage over chickpea + linseed and sole chickpea. Higher value of number of Helicoverpa larvae/10 plants, number of damaged pods/plant and pod damage percentage were recorded at 100% RDF than the lower levels of fertilizer but fails to exert significant effect on these indices except to pod damage percentage which were significantly more at 100% RDF than 50% RDF. Land equivalent ratio (LER) did not vary significantly among the row ratio in intercropping systems, only 6:1 row ratio of chickpea + mustard recorded significantly higher LER (1.15 and 1.16) over sole chickpea in both years. LER did not vary significantly among different fertilizer levels. Chickpea + mustard in 6:1 row ratio altogether recorded maximum chickpea equivalent yield (CEY) (2233 and 2501 kg ha-1) and net return (Rs. 44828 ha-1) however, B: C ratio (BCR) was higher under 6:2 row ratio of chickpea + mustard (2.10) which was at par with 6:1 row ratio of chickpea + mustard (2.08). Chickpea + mustard in both the row ratio recorded significantly higher CEY, net return and B:C ratio over chickpea + linseed in both the row ratio and sole chickpea. CEY, gross and net returns, BCR and LER did not varied significantly among the fertilizer levels.